Propuesta de implementación de un sistema de gestión integral de residuos sólidos apoyado con la norma ISO 14001:2015 en la planta de empacado de arándanos de la empresa HORTIFRUT TAL S.A.C. - Bazán Liñan, Roi Alberto (2019)
This research work begins with the obtaining of all existing and available information on the operation of solid waste management in the Blueberry Packing Plant of the Hortifrut TAL SAC Company, compliance with current environmental regulations and the ISO 14001: 2015 standard applicable to said organization, which gives us the establishment and the proposal of a solid waste management system based on the ISO 14001: 2015 standard. As a result of the evaluation that was made to the solid waste management of the Blueberry Packing Plant of the company Hortifrut TAL S.A.C., it was determined that it was inadequate and inefficient. Therefore, when applying the activities proposed in the following research work, the company will comply with current environmental regulations, help mitigate environmental impacts, adequately sustain internal and external audits, avoid fines in future supervisions and improve their competitiveness in the market